2016
DOI: 10.1016/j.psychsport.2015.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Using self-determination theory to understand motivation for walking: Instrument development and model testing using Bayesian structural equation modelling

Abstract: Objective: The motivational processes underpinning walking behaviour are not well understood. This study aimed to develop walking-specific motivation measures drawn from selfdetermination theory (SDT), assess the psychometric properties of the measures, incorporating Baysesian structural equation modelling (BSEM), and examine how these variables relate to walking behaviour.Method: Participants (n=298; mean age=41.69; S.D.=11.06; male =57) completed the Behavioural Regulations in Walking Questionnaire (BRWQ), P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 53 publications
2
50
0
Order By: Relevance
“…These findings build on the limited research that has investigated the relationship between motivation and incidental physical activity (Keatley et al ., ). Previous studies have found that autonomous motivation is associated with higher levels of intentional physical activity than controlled motivation, although controlled motivation has also been associated with engagement in health‐related behaviours (Chatzisarantis & Hagger, ; Chatzisarantis et al ., ; Hagger & Chatzisarantis, ; Hagger et al ., ; Niven & Markland, ; Webber et al ., ). Our finding here for incidental physical activity suggests that autonomous motivation and controlled motivation both contribute to behaviour engagement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings build on the limited research that has investigated the relationship between motivation and incidental physical activity (Keatley et al ., ). Previous studies have found that autonomous motivation is associated with higher levels of intentional physical activity than controlled motivation, although controlled motivation has also been associated with engagement in health‐related behaviours (Chatzisarantis & Hagger, ; Chatzisarantis et al ., ; Hagger & Chatzisarantis, ; Hagger et al ., ; Niven & Markland, ; Webber et al ., ). Our finding here for incidental physical activity suggests that autonomous motivation and controlled motivation both contribute to behaviour engagement.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, autonomous motivation has been associated with greater exercise engagement over time (Chatzisarantis & Hagger, ; Chatzisarantis, Hagger, Biddle, Smith, & Wang, ), and intentions to exercise (Hagger & Chatzisarantis, ; Hagger, Chatzisarantis, Culverhouse, & Biddle, ). However, recent research has also linked controlled motivation to engagement in health‐related behaviours, particularly when external pressures remain (Caudwell & Keatley, ; Niven & Markland, ). A recent systematic review of 53 exercise studies provided some support for the influence of controlled motivation on physical activity behaviour (Teixeira et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contrary to the SEAS analyses, the present analyses used BSEM, which allows more complex, and thus more realistic, models to be specified. BSEM was recently used by Niven and Markland (2016) to establish motivational factors in walking and was favored over the independent clusters model using a maximum likelihood approach to confirmatory factor analysis (ML-CFA ICM). The authors criticized the ML-CFA ICM approach because "ICM approach channels unspecified covariation between indicators through their factors, upwardly biasing interfactor correlations" (Niven & Markland, 2016, p. 97).…”
Section: Discussionmentioning
confidence: 99%
“…The analytical methods used in this study should also be seen as another strength of this article. It has been shown that BSEM is a more appropriate method than traditional CFA methods as it better reflects the complexities of reality (Niven & Markland, 2016;Stenling et al, 2015).…”
Section: Strengths and Limitationsmentioning
confidence: 99%